Nodular malignant melanoma in vulvar skin without pigmentation: a case report - Jing Nie; Yan Li; Xue Shen; Yan Liu; Haipeng Shi; Yonghong Lu (BMC, 2021)
Abstract Background Polypoid nodule growing without apparent pigmentation on the vulvar skin usually reminds us of the diagnostic pitfall, which is commonly and mistakenly diagnosed as other types of tumors. Although there are several manifestations of amelanotic melanoma are known, these malignancies are usually pigmented because they are derived from melanocytes containing melanin. However, amelanotic melanomas are easily misdiagnosed or their diagnoses were commonly delayed due to lack of pigmentation. Therefore, a solitary polypoid nodule is worth noting and further reporting. Particularly, the clinical characteristics and outcomes of the solitary polypoid nodule are rare in Asian patients. Case presentation We presented an interesting case of a 33-year-old female with a solitary polypoid nodule without apparent pigmentation on her vulvar skin. Her medical history was unclear, no ulcer was seen in the lesion area, and dermatoscopy was indicated a possible tumorous change, which has caught the attention of clinicians, and then further examined by the pathologist. The final diagnosis was nodular malignant melanoma (NM) (Breslow thickness 9.5mm, Clark level 4). Conclusions Hence, though reviewing this case record, the relevant literature and NM-related materials, we suggest that the combination of skin imaging technology and histopathological examination could provide us a better understanding and reduce the possibility of misdiagnosis in clinic practice.